Economic Integration And Environment In Organizing Ports Services (Management Of Juridical Analysis Of Tanjung Emas Port In Semarang) - Widya Putri Idayatama; Rakhmat Bowo Suharto (Jurnal Daulat Hukum, 2019)
The study "Economic Integration and Environment in organizing Ports Services (Management Of Juridical Analysis of Tanjung Emas Port in Semarang)" aims to: 1) analyze the economic and environmental integration in port management. 2) analyze the economic and environmental integration in the management of the harbor at the port of Tanjung Emas in Semarang. 3) analyze constraints identified in the waste management of Tanjung Emas In Semarang.Methods of research in this thesis using Legal Social approach. Reresearch socio-legal research is helping to understand and provide the social and political context configurations that affect the law and its implementation. Through interviews with officials in the relevant port of Tanjung Emas Port Semarang, or by observation in the form of observations systematically involved in obtaining the data. Afterwards will be analyzed data obtained from various sources qualitatively. The results showed that: 1) economic integration with the environment which is run by PT. Pelindo III Semarang as a form of sustainable develoRegulationent 2) based on field data. Pelindo participate in environmental protection activities with the implementation of the rules of environmental controls derived from ISO 14001: 2015 and the units participating in the supervisory activities of environmental conservation 3) barriers that exist in the management of waste in the port of Tanjung Emas is not only Pelindo remember their other business entities that participate in managing the port.Keywords: Economic Integration; Environment; Ports Services Management